Mathematical modelling of rice mill production by using cubic B-spline and discrete least square method / Siti Noorkhaliesa Che Pa - Che Pa, Siti Noorkhaliesa (2017)
As a developing country, the growth in per capita of Malaysia brings higher demand of rice, which is the main food in the country. The objective of this study is to observe the production pattern of rice at the chosen rice mill, which is BERNAS Pasir Puteh, Kelantan. Then, through the graph plotted by using cubic B-spline and discrete least square method, the production of the rice will be estimated and interpolated. By using data from the rice mill, both methods are applied to analyse them. This study obtains that both cubic B-spline and discrete least square methods can show the production patterns successfully and there is continuous supply of rice in Malaysia. However, by using Mean Square Error(MSE) and Root Mean Square Error(RMSE), it is concluded that B-spline method is more efficient than discrete least square method since it has the lower total RMSE.